The Effect of PAD and SiLPA on Opportunistic Behavior and Impact on Economic Growth - Andini, Mutiara Labiba; Moh. Khusaini (Sekolah Pascasarjana Universitas Brawijaya, 2023)
In implementing regional autonomy, the Regional Government is disposed to have the authority to take care of finances within one budget period. However, in budgeting, opportunistic behavior in budgeting is often found. It can be seen through determining PAD where the legislature increases targets for personal gain and does not consider the time and duration of APBD allocations which will cause SiLPA in the following year. This research will focus on the Regency/City of South Sumatra in 2017-2021. In addition, the population also influences economic growth. Where if the population is getting more significant, it is expected that economic growth will increase. Therefore the aim of this research is to find out the effect of PAD and SiLPA on opportunistic behavior and economic growth in the Regency/City of South Sumatra in 2017-2021. The research methodology uses Partial Least Square. The study found that PAD and SiLPA positively and significantly affected opportunistic budgeting. Furthermore, opportunistic budgeting and population have a positive but insignificant impact on economic growth.Keywords: local own-source revenue; budget surplus; opportunistic budgeting; population; economic growth